¿Who is going to consume the consumer arbitration?: the problematic case in favor of access to consume’s justice - Rodríguez García, Gustavo M. (2017)
Consumer arbitration seeks to resolve, on a voluntary, fast and legally binding way, conflicts between consumers and suppliers. Consequently, the consumers obtain a definitive solution to the problems arisen with companies in a much shorter term and even receiving compensation for damages. However, what happens when access to this procedure is no longer universal for all consumers?.In this article, the author reveals the problems surrounding access to consumer justice and to discover whether national mechanisms, as designed, actually achieve their protection objectives.